3m+7=-1m+3

Simple and best practice solution for 3m+7=-1m+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m+7=-1m+3 equation:


3m+7=-1m+3

We simplify the equation to the form, which is simple to understand
3m+7=-1m+3

We move all terms containing m to the left and all other terms to the right.
+3m+1m=+3-7

We simplify left and right side of the equation.
+4m=-4

We divide both sides of the equation by 4 to get m.
m=-1

See similar equations:

| 2(x-7)-3(x-4)=1 | | y+165+(8y-75)=180 | | 5+4(x-3)-3x=-11 | | V=(56)(68)(53) | | 5x+4x-39=26-4x | | -22=6+4x-9(x+2) | | 7x^2+62x=135 | | -74=8z | | 3x-10+4x-1=3 | | 8x+9x-100=50-8x | | -2y+1-9y+1+-22y+11+2=180 | | -6x+5(2x+4)=-8 | | 4xsqaured-3x+3=0 | | -7x+8+8x=7+x+1 | | 4*x^3+6*x=0 | | 2(x+5)=-3x+5(x+2) | | sqrt(6x-4)-1=sqrt(3x+1) | | 2n+36=-104 | | 4x+166=9x+236 | | 9a+5=77 | | y=2x^2+16x+24 | | -30=6p | | 28+25m=42+18 | | 5x+141=8x+171 | | 8(2l+6)=128 | | =6p | | 4x+5=5x-35 | | 5x-2+6y+7=180 | | 8(2l*6)=128 | | -0.5+0.25x=15-x | | 1x-9=9 | | 10+2(x-7)=-12 |

Equations solver categories